Clinical characteristics of non-intensive care unit COVID-19 patients in Saudi Arabia: A descriptive cross-sectional study - Awad Al-Omari; Waad N. Alhuqbani; Abdul Rehman Z. Zaidi; Maha F. Al-Subaie; Alanoud M. AlHindi; Ahmed K. Abogosh; Aljwhara K. Alrasheed; Aya A. Alsharafi; Mohammed N. Alhuqbani; Samer Salih; Mogbil A. Alhedaithy; Rayid Abdulqawi; et al. (Elsevier, 2020)
Introduction: The ongoing pandemic of the coronavirus disease 2019 (COVID-19) is a global health concern. It has affected more than 5 million patients worldwide and resulted in an alarming number of deaths globally. While clinical characteristics have been reported elsewhere, data from our region is scarce. We investigated the clinical characteristics of mild to moderate cases of COVID-19 in Saudi Arabia. Methods: This is a descriptive, cross-sectional study. Data of 401 confirmed COVID-19 patients were collected from 22 April 2020 to 21 May 2020 at five tertiary care hospitals in Riyadh, Saudi Arabia. The patients were divided into four groups according to age, Group 1: 0-<18 years, Group 2: 18-<50 years, Group 3: 50-60 years, and Group 4: >60 years; and their clinical symptoms were compared. Results: The median (IQR) age in years was 10.5 (1.5−16) in group I, 34 (29−41) in group II, 53 (51−56) in group III, and 66 (61−76) in group IV. Most patients were male (80%, n = 322) and of Arabian or Asian descent. The median length of stay in the hospital was 10 (8-17) days (range 3-42 days). The most common symptoms were cough (53.6%), fever (36.2%), fatigue (26.4%), dyspnea (21.9%), and sore throat (21.9%). Hypertension was the most common underlying comorbidity (14.7%), followed by obesity (11.5%), and diabetes (10%). Hypertensive patients were less likely to present with shortness of breath, cough, sputum, diarrhea, and fever. Conclusion: There was no significant difference in the symptoms among different age groups and comorbidities were mostly seen in the older age group. Interestingly, hypertensive patients were found to have milder symptoms and a shorter length of stay. Further larger collaborative national studies are required to effectively understand clinical characteristics in our part of the world to efficiently manage and control the spread of SARS-CoV-2.